Response to Jin Hyun Kim - Dynamics of Musical Expression - Doantan-Dack, Mine (Empirical Musicology Review, 2013)
This commentary focuses on three aspects of the experience of musical expressiveness as a dynamically emergent phenomenon: the nature of the experience itself, the nature of the dynamic forms of music, and the process of shaping music expressively in the act of music-making.